2010
DOI: 10.1158/1535-7163.mct-10-0300
|View full text |Cite
|
Sign up to set email alerts
|

BNP7787-Mediated Modulation of Paclitaxel- and Cisplatin-Induced Aberrant Microtubule Protein Polymerization In vitro

Abstract: Taxane and platinum drugs are important agents in the treatment of cancer and have shown activity against a variety of tumors, including ovarian, breast, and lung cancer, either as single agents or in combination with other chemotherapy drugs. However, a serious and prevalent side effect of taxane (docetaxel and all formulations/derivatives of paclitaxel) and platinum (cisplatin, carboplatin, and oxaliplatin) agents is dose-limiting chemotherapy-induced peripheral neuropathy (CIPN). CIPN can result in treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Some clinical data, with different levels of reliability (Table 3), indicated that amifostine exerts some protection against peripheral neurotoxicity of carboplatin plus paclitaxel combination therapy [127][128][129]131], oxaliplatin [126], and cisplatin [133,134], whereas two other studies have failed to show significant neuroprotection against carboplatin plus paclitaxel combination therapy [130] and cisplatin [132] (Table 3). BNP7787 (Dimesna, Tavocept, 2,29-dithio-bis-ethanesulfonate) has also shown some cytoprotective activities in vitro [174]. This effect was not confirmed in the clinical setting, although the study was unblinded with no placebo-controlled group and high risk of bias [135].…”
Section: Detoxicantsmentioning
confidence: 99%
“…Some clinical data, with different levels of reliability (Table 3), indicated that amifostine exerts some protection against peripheral neurotoxicity of carboplatin plus paclitaxel combination therapy [127][128][129]131], oxaliplatin [126], and cisplatin [133,134], whereas two other studies have failed to show significant neuroprotection against carboplatin plus paclitaxel combination therapy [130] and cisplatin [132] (Table 3). BNP7787 (Dimesna, Tavocept, 2,29-dithio-bis-ethanesulfonate) has also shown some cytoprotective activities in vitro [174]. This effect was not confirmed in the clinical setting, although the study was unblinded with no placebo-controlled group and high risk of bias [135].…”
Section: Detoxicantsmentioning
confidence: 99%
“…BNP7787 is expected to remain predominantly in the disulfide form in the plasma; 6 , 10 , 32 however, the intracellular environment and the interstitial space are likely venues for BNP7787 metabolism to mesna, mesna-disulfide heteroconjugates, and free thiols. Any of these species (BNP7787, intracellularly generated BNP7787-derived mesna, or BNP7787-derived mesna-disulfide heteroconjugates) may modify proteins in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action, safety, effectiveness, and potential for tumour protection of this agent have been extensively evaluated using in vitro and in vivo models (Parker et al, 2010).…”
Section: Tavocept (Disodium 22´-dithiobisethane Sulfonate Bnp7787 mentioning
confidence: 99%